Diversity of medicinal plant by Talang Mamak tribe in surrounding of Bukit Tiga Puluh National Park, Riau - FRANCISCA MURTI SETYOWATI; WARDAH WARDAH (Society for Indonesian Biodiversity, 2007)
Local peoples in a certain area is very depends on plants grow on surrounding them for fulfill daily lifelyhoat such as food, clothing, construction material, medicinal, etc. People knowledge in plants utilized especially as medicinal matter was passed on from generation to generation. Documentation and conservation of traditional knowledge from the local people until to do the research of diversity of medicinal plant by Talang Mamak tribe in Bukit Tigapuluh National Park, Riau. Field data collection of medicinal plants was done by directobservation and interview with the figure or tribe-head and community is used medicinal plant in surrounding them. From the survey it result that at least 77 species of plants are used as medicines. Five species from these was categorised as endangered species such as pulai (Alstonia scholaris), gaharu (Aquilaria malaccensis), kapung-kapung (Oroxylum indicum), pasak bumi (Eurycoma longifolia), and akar kuning (Arcangelisia flava). Kinds of diseases can be cover with ingredient of traditional medicines, the process and method, part of plant used, and species having potency for develop in the future is discussed in this paper.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Medicinal plant, Talang Mamak tribe, Bukit Tigapuluh National Park, Riau